VMXi: a fully automated, fully remote, high‐flux in situ macromolecular crystallography beamline. (23rd November 2018) - Sanchez-Weatherby, Juan; Sandy, James; Mikolajek, Halina; Lobley, Carina M. C.; Mazzorana, Marco; Kelly, Jon; Preece, Geoff; Littlewood, Rich; Sørensen, Thomas L.-M.
Abstract : VMXi, a new tunable beamline dedicated to fully automatic screening and data collection from crystals in situ, is reported. Abstract : VMXi is a new high‐flux microfocus macromolecular crystallography beamline at Diamond Light Source. The beamline, dedicated to fully automated and fully remote data collection of macromolecular crystals in situ, allows rapid screening of hundreds of crystallization plates from multiple user groups. Its main purpose is to give fast feedback at the complex stages of crystallization and crystal optimization, but it also enables data collection of small and delicate samples that are particularly difficult to harvest using conventional cryo‐methods, crystals grown in the lipidic cubic phase, and allows for multi‐crystal data collections in drug discovery programs. The beamline is equipped with two monochromators: one with a narrow band‐pass and fine energy resolution (optimal for regular oscillation experiments), and one with a wide band‐pass and a high photon flux (optimal for fast screening). The beamline has a state‐of‐the‐art detector and custom goniometry that allows fast data collection. This paper describes the beamline design, current status and future plans.